F2-Isoprostanes: A Measure of Oxidative Stress in Children Receiving Treatment for Leukemia. (July 2014) - Hockenberry, Marilyn J.; Taylor, Olga A.; Gundy, Patricia M.; Ross, Adam K.; Pasvogel, Alice; Montgomery, David; Ribbeck, Phillip; McCarthy, Kathy; Moore, Ida
Acute lymphoblastic leukemia (ALL) is the most prevalent and curable cancer among children and adolescents less than 15 years of age in the United States. Essential for cure of childhood ALL is prophylactic treatment of the central nervous system (CNS), with methotrexate (MTX) being the most widely used drug in this treatment. While CNS treatment has contributed to long-term disease-free survival, resulting declines in academic abilities have been reported. There is growing evidence that CNS treatment with MTX increases oxidative stress, a potential mechanism of CNS injury. This article reports changes in oxidative stress, measured by the biomarker F2 -isoprostane (F2 -IsoP), in the cerebrospinal fluid (CSF) in 47 children with ALL during the first 18 months of treatment. The number of CSF samples ranged from 5 to 14 during postinduction and from 1 to 9 during continuation. Total doses of intrathecal MTX during postinduction were significantly correlated with the mean and highest concentrations of F2 -IsoP during postinduction and the mean concentration of F2 -IsoP during continuation. F2 -IsoP concentrations during postinduction and continuation were higher in children who received more than six doses of intrathecal MTX. New therapies for a highly curable disease such as childhood leukemia have the potential to be individualized in the future, requiring reliable molecular and biochemical markers, such as oxidative stress indicators. Innovative use of biomarkers has the potential to increase our understanding of treatment-related toxicities and associated symptoms and to inform future therapeutic approaches for optimizing cure and quality of life among children with leukemia.